A240 AN UNUSUAL PRESENTATION OF HEPATIC ENCEPHALOPATHY: RECURRENT GLOBAL APHASIA. (1st March 2018) - Wishart, E; Block, H; Bedi, A
Abstract: Background: Hepatic encephalopathy (HE) is impairment in a brain function caused by liver dysfunction and portosystemic shunting. It is a frequent and debilitating complication of cirrhosis, the pathophysiology of which is complex and not fully elucidated. HE is associated with poor survival and has a high risk of recurrence. Hepatic encephalopathy can present as a wide spectrum of neurological and psychiatric abnormalities ranging from subclinical alterations to coma and death. Despite the wide range of presentations there have been no published cases of hepatic encephalopathy presenting as global aphasia. Aims: We describe a case of a patient with alcoholic cirrhosis with recurrent presentations of HE presenting as global aphasia. Methods: A case of HE with global aphasia is reviewed and literature review on HE with focal findings is explored and summarized. Results: A 57 y/o F with decompensated alcoholic cirrhosis presents to hospital with acute onset global aphasia. Her past medical history is significant for two previous left parieto-occipital lobe hemorrhagic strokes and medically controlled seizures after these strokes. CT/CTA showed no acute changes consistent with stroke and EEG demonstrate triphasic waves consistent with metabolic derangement. Serum ammonia was elevated at 136 μmol/L. On collateral history the patient was reported to be non-compliant with lactulose. The patient was restarted on lactulose in hospital and quickly improved to baseline. 6 months later the patient presented again with global aphasia. A CT ruled out stroke and HE was found to be responsible for her aphasia with an ammonia of 106 μmol/L. Her HE was precipitated by an upper gastrointestinal bleed and ongoing alcohol use. EGD revealed portal hypertensive gastropathy, gastric ulcers, and small varices not amenable to banding. Paracentesis was completed to rule out spontaneous bacterial peritonitis and ultrasound ruled out hepatocellular carcinoma. Rifaxamin was added to the patients' medication regime and her symptoms resolved. Conclusions: In this case, we present a review on the literature of HE presenting with focal deficits. Despite the wide range of presentations of HE with focal neurologic signs - including hemiplegia, hemiparasia, hemiagnosia, abnormal extraocular movements, and apraxias - there have been no published cases of hepatic encephalopathy presenting as global aphasia. This is the first documented case of global aphasia being the focal neurological sign in HE. Alternatively, we postulate that the encephalopathy brought out the patient's deficits from her prior left parieto-occipital strokes. Funding Agencies: None